Mastering ninject for dependency Injection : learn how ninject facilitates the implementation of dependency injection to solve common design problems of real-life applications /: learn how ninject facilitates the implementation of dependency injection to solve common design problems of real-life applications. (2013) - Unknown
No abstract available